Asia Pacific Business Process Management First Asia Pacific Conference, AP-BPM 2013, Beijing, China, August 29-30, 2013, Selected Papers - Song, Minseok; Wynn, Moe Thandar; Liu, Jianxun (Lecture Notes in Business Information Processing, 2013)
This book constitutes the proceedings of the First Asia Pacific Conference on Business Process Management held in Beijing, China, in August 2013. In all, 19 contributions from seven countries were submitted. Following an extensive review process by an international Program Committee, seven full papers and one short paper were accepted for publication in this book and presentation at the conference. In addition, a keynote by Wil van der Aalst is also included.